2010
DOI: 10.1103/physrevc.81.044321
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic-macroscopic approach for binding energies with the Wigner-Kirkwood method

Abstract: The semiclassical Wigner-Kirkwoodh expansion method is used to calculate shell corrections for spherical and deformed nuclei. The expansion is carried out up to fourth order inh. A systematic study of Wigner-Kirkwood averaged energies is presented as a function of the deformation degrees of freedom. The shell corrections, along with the pairing energies obtained by using the Lipkin-Nogami scheme, are used in the microscopic-macroscopic approach to calculate binding energies. The macroscopic part is obtained fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 70 publications
1
93
1
Order By: Relevance
“…Next, we calculate single-particle (SP) levels in each nucleus by using a Woods-Saxon potential, whose parameters are taken from Ref. [10]. Note that, in principle, the SP potential depends on temperature.…”
Section: Finite-temperature Shell-correction Methodsmentioning
confidence: 99%
“…Next, we calculate single-particle (SP) levels in each nucleus by using a Woods-Saxon potential, whose parameters are taken from Ref. [10]. Note that, in principle, the SP potential depends on temperature.…”
Section: Finite-temperature Shell-correction Methodsmentioning
confidence: 99%
“…In our previous works [6,7], we have demonstrated that the Strutinsky average can be replaced by the semiclassical energy computed by means of the Wigner-Kirkwood (WK)h expansion of the one-body partition function [8][9][10][11][12][13][14][15], in order to evaluate the shell corrections of a system of N neutrons and Z protons at zero temperature in an external potential. There are some reasons supporting this choice as we have discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Thus ETF energy functional embodies the macroscopic models; it is more general and powerful. Some of the macroscopic models with microscopic corrections [48,50,54,55,60, and 81] also suffer from the inconsistency problem mentioned earlier. Exceptions being the Duflo-Zuker…”
Section: Further Discussionmentioning
confidence: 99%
“…These are the same set of nuclei considered by Bhagwat et al [54]. The electronic binding energy 1.433x10 −5 Z 2.39 MeV has been subtracted from the binding energies of Ref [38].…”
Section: A Calculations For Nucleimentioning
confidence: 99%
See 1 more Smart Citation